1997
DOI: 10.1074/jbc.272.37.23172
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Heparan Sulfate Depends on 2-O-Sulfation of Uronic Acids

Abstract: To study how the pattern of sulfation along a heparan sulfate chain affects its turnover, we examined heparan sulfate catabolism in wild-type Chinese hamster ovary cells and mutant pgsF-17, defective in 2-O-sulfation of uronic acid residues (Bai, X., and Esko, J. D. (1996) J. Biol. Chem. 271, 17711-17717). Heparan sulfate from the mutant contains normal amounts of 6-O-sulfated glucosamine residues and iduronic acid and somewhat higher levels of N-sulfated glucosamine residues but lacks any 2-O-sulfated iduroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 53 publications
(83 reference statements)
2
40
0
Order By: Relevance
“…Moreover, heparin with low affinity for antithrombin was degraded by heparanase to about the same extent as high affinity heparin, despite an ϳ10-fold lower content of GlcN 3-O-sulfate groups (39). Finally, Bai et al (16) recently found aberrant turnover of HS in CHO cells defective in a sulfotransferase required for 2-O-sulfation of hexuronic acid residues and concluded that 2-O-sulfated IdceA units are important for cleavage of HS by intracellular heparanase. 3 The results of the present study suggest that the single 2-O-sulfated hexuronic acid unit required for substrate recognition by the heparanase may be either GlcUA or IdceA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, heparin with low affinity for antithrombin was degraded by heparanase to about the same extent as high affinity heparin, despite an ϳ10-fold lower content of GlcN 3-O-sulfate groups (39). Finally, Bai et al (16) recently found aberrant turnover of HS in CHO cells defective in a sulfotransferase required for 2-O-sulfation of hexuronic acid residues and concluded that 2-O-sulfated IdceA units are important for cleavage of HS by intracellular heparanase. 3 The results of the present study suggest that the single 2-O-sulfated hexuronic acid unit required for substrate recognition by the heparanase may be either GlcUA or IdceA.…”
Section: Discussionmentioning
confidence: 99%
“…Endoglycosidases capable of partially depolymerizing HS chains have been demonstrated in a variety of cells and tissues, such as placenta (7), skin fibroblasts (8), platelets (9), melanoma (10), lymphoma (11), hepatocytes (12), CHO cells (13), and endothelial cells (14). Such enzymes, commonly referred to as "heparanases," contribute to the intracellular degradation of HS proteoglycans (15,16) but are also released into the extracellular matrix, where they appear to modulate several processes of pathophysiological importance. Heparanases thus contribute to the remodeling of extracellular matrix and basement membranes prerequisite to angiogenesis (17) and to the egress of metastatic tumor cells (18) and other types of blood-borne cells (19) from the vasculature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A CHO cell mutant, pgsF-17, defective in HS2ST, produces HS chains lacking not only IdoA(2-O-sulfate)-N -sulfoglucosamine and IdoA(2-O-sulfate)-N -sulfoglucosamine(6-O-sulfate) but also GlcA(2-O-sulfate)-N -sulfoglucosamine (83). When the HS2ST cDNA is transfected into the mutant cells, the synthesis of these structures is restored (84). A gene trap mutation for HS2ST causes renal agenesis and neonatal lethality in mutant mice (85).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 99%
“…35 S]GAGs recovered from the cultures 1-2 days after temperature shift presumably reflects partial turnover of membrane proteoglycans through endocytosis and lysosomal degradation (28,29).…”
Section: Resultsmentioning
confidence: 99%